2000
DOI: 10.1038/sj.gt.3301339
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-enhanced ultrasound for vascular gene delivery

Abstract: Progress in cardiovascular gene therapy has been hampered by concerns over the safety and practicality of viral vectors and the inefficiency of current nonviral transfection techniques. We have previously reported that ultrasound exposure (USE) enhances transgene expression in vascular cells by up to 10-fold after naked DNA transfection, and enhances lipofection by up to three-fold. We report here that performing USE in the presence of microbubble echocontrast agents enhances acoustic cavitation and is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
178
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(186 citation statements)
references
References 34 publications
7
178
1
Order By: Relevance
“…The present study confirmed the previous observation that, ultrasound exposure in the presence of microbubble echo-contrast agents enhances acoustic, cavitation and is associated with approximately 300-fold increments in transgene expression after, naked DNA transfection in in vitro experiments. 38 Of importance, plasmid DNA transfection using ultrasound was markedly improved by a microbubble enhancer, Optison. The increase in transfection efficiency might be due to the appearance of transient holes in the cell membrane caused by spreading of the bubbles.…”
Section: (B) Effect Of Transfection Of Human Hgf Plasmid On Number Ofmentioning
confidence: 99%
“…The present study confirmed the previous observation that, ultrasound exposure in the presence of microbubble echo-contrast agents enhances acoustic, cavitation and is associated with approximately 300-fold increments in transgene expression after, naked DNA transfection in in vitro experiments. 38 Of importance, plasmid DNA transfection using ultrasound was markedly improved by a microbubble enhancer, Optison. The increase in transfection efficiency might be due to the appearance of transient holes in the cell membrane caused by spreading of the bubbles.…”
Section: (B) Effect Of Transfection Of Human Hgf Plasmid On Number Ofmentioning
confidence: 99%
“…[29][30][31][32] The sonication procedure was feasible in the present study, and the animals tolerated the 1 min sonication with focused ultrasound well. Visible mild adverse effects such as punctate hemorrhage were dose dependent and occurred above a threshold pressure of 6.3 MPa, while severe adverse effects such as puncturing of the artery were observed above 10 MPa pressure amplitude in the presence of cavitation contrast agent bubbles.…”
Section: Discussionmentioning
confidence: 66%
“…26,[29][30][31][32] Cavitation involves the formation of gaseous bubbles, a few micrometers in diameter, because of a disruption of the propagation medium by the negative pressure cycle in ultrasonic fields. 38 These cavitation bubbles can oscillate in response to ultrasound fields, possibly influencing the surrounding structures such as membranes.…”
Section: Discussionmentioning
confidence: 99%
“…1 We have previously demonstrated up to 10-fold enhancements in gene delivery to primary vascular smooth muscle cells (VSMC) and endothelial cells following ultrasound exposure (USE) in vitro, 2 increasing to up to 500-fold in the presence of echocontrast microbubbles (ECM). 3 The challenge for this technology remains the demonstration that it is 'sufficiently efficient' for therapeutic gene delivery in clinically relevant animal models of cardiovascular disease. Prevention of late saphenous vein graft (SVG) failure is an attractive and important target for therapeutic gene delivery and offers the opportunity for ex vivo manipulation of the vein prior to grafting into the coronary or peripheral circulation.…”
mentioning
confidence: 99%
“…Transfections with the luciferase plasmid pGL3 (Promega, Southampton, UK) were performed in 24-well plates using a custom-built USE system (AFB) as described previously. 3 USE was performed at 1 MHz for 60 s at a mechanical index (MI) of 1.8, 6% duty cycle (DC), where applicable in the presence of varying concentrations (10-50% (v/v)) of the ECM SonoVue s or BR14 (4 Â 10 8 bubbles/ml stock, gifts from Bracco Research, Geneva) or Optisont (5 Â 10 8 bubbles/ml stock, Amersham Health, Bucks, UK). Luciferase activity in cell lysates was measured after 48 h as described previously 3 using an LB953 AutoLumat PLUS luminometer (Berthold Technologies UK Ltd, Redbourn, Herts, UK) and expressed as light units (LU)/mg total cell protein (BioRad protein assay kit, BioRad Laboratories, Munich, Germany).…”
mentioning
confidence: 99%